Renina Katz e Virgínia Artigas: gravuras políticas na imprensa comunista - Hermenegildo Júnior, Gabriela (2021)
This dissertation consists of a research on two Brazilian printmakers during the 1940s and 1950s, who published their prints in the communist press linked to the Brazilian Communist Party: Renina Katz and Virgínia Artigas. Through an historical, social and gender lense, the engravings of the artists published in the Brazilian communist periodicals Voz Operária, Imprensa Popular, Momento Feminino and Revista Fundamentos will be analyzed. The central objective is to discuss the places of these women artists in the Brazilian communist press that illustrated themes considered social and revolutionary. The research analyzes the visual productions published by the periodicals, understanding the role of these female artists at the time they were published in the press and also in contemporary art history. The main authors used for this research were Dênis de Moraes (1994), Aracy Amaral (1987), Walter Benjamin (2012), Griselda Pollock (1988), Linda Nochlin (1988), Madalena Zaccara (2017) and Rosa Artigas (2019).